2006
DOI: 10.1074/jbc.m510957200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipid Metabolism Genes, Lipid Carrier Protein Lipophorin, and Its Receptor during Immune Challenge in the Mosquito Aedes aegypti

Abstract: In the mosquito Aedes aegypti, the expression of two fat body genes involved in lipid metabolism, a lipid carrier protein lipophorin (Lp) and its lipophorin receptor (LpRfb), was significantly increased after infections with Gram (؉) bacteria and fungi, but not with Gram (؊) bacteria. The expression of these genes was enhanced after the infection with Plasmodium gallinaceum. RNA interference (RNAi) knockdown of Lp strongly restricted the development of Plasmodium oocysts, reducing their number by 90%. In Vg-⌬R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 52 publications
3
84
1
2
Order By: Relevance
“…In addition, GATA4 in conjunction with NF-B transcription factors were found to be required for induction of lipophorin receptor gene involved in A. aegypti systemic immune responses and lipid metabolism (32). In insects, lipophorin is the main lipid carrier protein transporting lipids to various tissues and is also involved in immune responses (32,33). It is not clear at this stage how upregulation of GATA4 by KUNmiR-1 or Wolbachia may facilitate WNV gRNA replication in mosquito cells, and this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GATA4 in conjunction with NF-B transcription factors were found to be required for induction of lipophorin receptor gene involved in A. aegypti systemic immune responses and lipid metabolism (32). In insects, lipophorin is the main lipid carrier protein transporting lipids to various tissues and is also involved in immune responses (32,33). It is not clear at this stage how upregulation of GATA4 by KUNmiR-1 or Wolbachia may facilitate WNV gRNA replication in mosquito cells, and this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…GATA4, specifically, is expressed after a blood meal and acts as a transcriptional activator of vitellogenin (vg), which is an important protein in vitellogenesis and egg development (31). In addition, GATA4 in conjunction with NF-B transcription factors were found to be required for induction of lipophorin receptor gene involved in A. aegypti systemic immune responses and lipid metabolism (32). In insects, lipophorin is the main lipid carrier protein transporting lipids to various tissues and is also involved in immune responses (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…42 Pathogen infections can activate a lot of immune factors expressed in mosquito fat body. [43][44][45][46][47][48][49] Therefore, immune response may play an important role in the process of DENV infection in mosquito fat body. Our results indicated that DENV-2 infection in fat body may induce rapid immune response at early times post-infection that can suppress virus replication in low level and protect fat body and even other organs from damage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have shown lipid uptake by the malaria parasite during its life cycle in the invertebrate host [49]. Molecular evidence for the role of Lp in malaria parasite development has been provided [50]. However, the direct uptake of Lp and lipids by malaria parasite stages while inside its vector are not available.…”
Section: Introductionmentioning
confidence: 99%